The language choice among Chinese-Indian mixed-marriage families in Malaysia - Ainun Rozana Mohd. Zaid; Yin Mee Mac (Journal of Modern Languages)
In Malaysia, under certain cultural, social and political conditions, a minority community might adopt a different language and become monohngual, bilingual or multilingual. However, the morc general trend, especially among well-educated individuals, is that they tend to become English speakers. This may occur among children from inter-group marriages where English is the only common language between the spouses. The main objective of this study is to examine the language choice among Malaysian children from inter-group marriages where one of the spouses is either Tamil or Chinese. Another objective IS to identify the role of attitude in language choice. The Chindians comprise dyads of Indian-Chinese mixed marriage children and their parents from urban areas. The data will be gathered through questionnaires and structured interviews administered across both groups. Analyses of the data will include a comparison of the language choice among the Chindians in the urban areas and the role of language as a marker of self/group Identity. The domains examined are home, school, workplace and places of worship.